Relationship between painful manifestations and the use of hydroxyurea in children and adolescents with sickle cell disease (Research, Society and Development, 2020)
To analyze the profile of pain, its triggering factors, and the relationship with the use of hydroxyurea in children and adolescents with sickle cell disease. This was an analytical cross-sectional study of 80 patients with sickle cell disease, both male and female, aged 6 to 18 years, seen at the Center for Hematology and Hemotherapy of Pernambuco, Brazil. To assess the pain profile, forms with the adapted visual scale from the “Fear of Dental Pain Questionnaire – Short Form” were used. Fisher's exact test was used to evaluate the association between pain manifestations and the use of hydroxyurea. Pain was reported by 68.7% of the patients and 52.7% of them reported severe pain, which eventually affected their daily routines. Physical triggers presented the highest rate (78.2%). The most frequent sites of pain were the trunk (80%) and lower extremities (54.5%), and constricting (40%) and deep (40%) pain were the most frequent types. Thirty percent of the patients reported being treated with hydroxyurea for prevention of painful events. It is concluded that the patients with sickle cell disease showed a high rate of painful events and physical factors, such as cold temperature, trauma and physical effort, were considered to be the most prevalent. There was no association between the use of hydroxyurea and pain improvement.